2016
DOI: 10.21554/hrr.041610
|View full text |Cite
|
Sign up to set email alerts
|

Urban Primacy in Urban System of Developing Countries; Its Causes and Consequences

Abstract: In the current world, cities have become the main arms of the actuator in the movement of social system of human communities. Nevertheless, urban systems in developing countries, despite the vast potentials, are faced with serious problems such as rapid urbanization, constant migration of rural people to cities, and concentration of population and activities in one or two cities, or, in other words, urban macrocephaly. Despite the primacy or dominance of one city in some developed countries, we do not observe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Such patterns have been identified in Asian countries such as Bangladesh (Bryan et al, 2014, Lagakos et al, 2023, the Philippines (Abarcar andTheoharides, 2021, Theoharides, 2018) and are likely to be observed in other countries such as Thailand or Indonesia (Swerts and Denis, 2015). Similar patterns of "urban macrocephaly" emerge in Latin American countries such as Colombia, Peru or Guatemala (Faraji et al, 2016).…”
Section: Discussionmentioning
confidence: 61%
“…Such patterns have been identified in Asian countries such as Bangladesh (Bryan et al, 2014, Lagakos et al, 2023, the Philippines (Abarcar andTheoharides, 2021, Theoharides, 2018) and are likely to be observed in other countries such as Thailand or Indonesia (Swerts and Denis, 2015). Similar patterns of "urban macrocephaly" emerge in Latin American countries such as Colombia, Peru or Guatemala (Faraji et al, 2016).…”
Section: Discussionmentioning
confidence: 61%
“…The two main cities, Tangier and Tetouan, as well as the neighboring municipalities, have accounted for most of the growth. This is a case of urban macrocephaly, which is typical in developing countries (Faraji et al 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Primacy is not considered a hallmark in egalitarian societies and democratic countries. Faraji et al (2016) identified political centralization and less democratic forms of government to be consistent with the existence of urban primacy.…”
Section: Introductionmentioning
confidence: 99%